IMPLEMENTASI BABY MONITOR UNTUK PENGAWASAN DAN PENGELOLAAN KEGIATAN DI LABORATORIUM MULTIMEDIA IAIN SURAKARTA - Syahirul Faiz (Integrated Lab Journal, 2018)
The increasing demands of innovation in learning methods led to an increase in the intensity of computer usage, including in multimedia laboratory at IAIN Surakarta. It is characterized by the increased amount of usages, not only for regular activities, such as practicum but also for non-regular activities such as training and computer-based test. Supervision for such activities is necessary because of the limited human resources to oversee the activity and a large number of computers and electronic devices which have to be watched. In addition to surveillance, an audio-visual tool is required to manage these activities remotely to replace human roles due to the limited human resources. One solution to overcome these problems is to install a baby monitor in the laboratory to monitor the computers and to manage certain activity remotely. This is done by implementing baby monitor and controlling it through an app called CMSClient (for desktop) and Yoosee (for Android). Based on the results of the experiments conducted, it can be concluded that the tools and applications can help the human to supervise and manage activities in the laboratory. Some of the functions provided by such devices and apps are live streaming, video playback, two-way audio, motion detector, and alarm notification.